Occurrence of a Fruit Spot Disease of Pear Caused by Septoria pyricola in Tyrnavos Larissa, Northern Greece - Thomidis, T (Plant disease, 2014)
Pear tree (Pyrus communis) is an important crop in Greece. In 2012, fruits of the pear cv. Kontoula were observed in commercial fields located in Tirnavos, Prefecture of Larrisa, Greece, with symptoms of well-defined brown angular margins and their grayish white centers in which a few pycnidia (about 180 × 150 μm) were produced within the spots. Pycnidia were dark, separate, and globe-shaped with an ostiole (opening at the apex) from which conidia (about 40 to 60 × 3 μm) were extruded, and erupted through the surface of the infected tissue. Conidia were produced on short conidiophores. They were clear, narrowly elongated to filiform, and several-celled. The pathogen was isolated on acidified-PDA (2.5 ml 85% lactic acid per liter of nutrient medium) and incubated at 23°C for 7 days. The pathogen was identified as Septoria pyricola Desm. based on morphological characteristics. Koch's postulates were completed in the laboratory by placing a 40-μl drop of suspension (4 × 105 conidia ml-1 of water) on a wounded area of healthy fruits of cv. Kontoula. Fruits were surface sterilized with dipping in 0.1% chlorine solution, allowed to dry in a laminar flow hood. There were 15 inoculated and 15 control fruits (similarly inoculated with sterile distilled water) in a randomized design. Fruits were covered with perforated polythene bags to maintain a high humidity necessary for infection and these bags were removed 48 h after inoculation and maintained at room temperature (23 ± 2°C). Lesion development was recorded daily for each fruit. Koch's postulates were satisfied after re-isolating the fungus from inoculated fruit that developed symptoms similar to those observed on fruits collected from fields. Symptoms of this disease were found in all pear orchards cultivating the cv. Kontoula located in Tyrnavos (a municipality in the Prefecture of Larissa). Symptoms of septoria leaf spot were also observed in the above pear orchards. In contrast, no symptom of septoria fruit spot and septoria leaf spot was observed in apple orchards of the above regions. To our knowledge, this is the first report of the occurrence of S. pyricola as causal agent of fruit spot of pears in Greece. Fruit spotting is relatively uncommon; nevertheless, Sivanesan (3) gives two reports of conidia infecting pear fruits from Italy and South Africa (1,2). References: (1) G. Florenzano. Int. Bull. Plant Prot. 20:17, 1946. (2) A. J. Louw. Farming in South Africa 23:737, 1948. (3) A. Sivanesan. IMI Descriptions of Fungi and Bacteria, vol. 99, sheet 989. CABI, Wallingford, UK, 1990